(untitled) - Philippine Bible Society (Philippines, 2007)
This is the first Greek-Tagalog Interlinear Bible using the texts from Ang Biblia (2001 Edition) and the United Bible Societies Greek New Testament as parsing guides. Scholars who want to learn more about Bible translation will find this useful. Features: The text of the UBS Greek New Testament The first-ever Tagalog interlinear gloss an analytical guide to the text of Ang Biblia. This is a great Christian product sourced from BIML - Bible in My Language, the leader in foreign language Bibles and outreach materials from Baltimore, Maryland in the USA. BIML stocks Bibles in more than 600 languages.
Keywords: Bible -- New Testament -- Interlinear translations